Implementation of Islamic Business Ethics in Increase welfare Trader Post Pandemic ( Study The case on UMKM Lamongan ) - Miftahal Anjarsabda Wira Buana; Akmalur Rijal; Moh. Ah. Subhan ZA; Khotijatul Khoiriyah (JOURNAL OF SHARIA ECONOMICS, 2023)
In economy Islamic , business And ethics No must looked at as two opposites , cause business which is symbol from affairs mundane is also considered as integral part of things that are investment afterlife . That is , if orientation business And effort investment hereafter ( intended as worship And is totality obedience to God ), then business with itself must in line with based on moral principles faith to afterlife . Even in Islam , understanding that business Alone No restricted affairs world , however covers all activity We in world that is " businessed " ( intended as worship ) for reach profit or reward afterlife .This research is a field research that uses a quantitative approach, namely analyzing data in the form of numbers. The data used in this research is primary data. Primary data is data directly obtained from the first data source at the research location.The process begins with theory, then by using deductive logic a research hypothesis is derived accompanied by measurement and operationalization of the concept, then empirical generalizations that rely on statistics so that it can be concluded as research findings. The research was conducted in the District Lamongan and research conducted from July to August 20 22 . The population is all the characteristics that are the object of research, where these characteristics are related to all groups of people, events or objects that are the center of attention for researchers. The population in the study were 54 entrepreneurial actors.Based on the results of the study, it was found that there was an influence of Islamic business ethics on business profits. Every Muslim trader must carry out his economic activities based on sharia, namely the rules or regulations that Allah commands His servants. The economic activity is interpreted as an activity that does not commit deception, there is justice between the seller and the buyer, there is generosity, has good motivation in running his business and all of that is only to carry out the commands of Allah SWT.By looking at the research results and several expert opinions, that basically business ethics highlights the moral behavior of humans who have a profession in the business field and are owned globally by business actors in general, while the embodiment of business ethics that exists in each business actor is formed and manifested according to the culture in question. This business ethics will emerge when each business actor relates and interacts with one another as a stakeholder . The purpose of business ethics here is to arouse the moral awareness of business people to run a business properly and cleanly. Based on the purpose of business ethics, business